A pilot study on the efficiency of a portable ozone generator in sterilizing dental instruments - Lareza, Lucia Bernadette S.
Ozone is an unstable triatomic form of oxygen that possesses antimicrobial properties due to its high oxidation potential. It must be generated at the point of application because it rapidly and spontaneously decomposes. In 1999, a portable generator of ozone was developed in the Philippines that was asserted by the manufacturer to have potential application in dental instrument sterilization. The objective of this pilot study was to determine whether sterilization of dental instruments can be achieved by submerging it in ozonated water using this ozone-generating device. For this purpose, the researcher used a qualitative type of experiment. Dental handpiece burs were inoculated with Bacillus subtilis in brain heart infusion broth (BHI) with a turbidity of 2.0 McFarland. The stainless steel burs were submerged in 500 m!_. distilled water in a glass vessel. The water was then ozonated using the ozone-generating unit. After specific time intervals 5-, 30- and 60 min), a bur was removed from the water and cultured. One ml_. of the broth was dropped in a nutrient agar plate. Three replicas were done for each time interval. Five ml_ of water from the vessel was also cultured and plated after every time interval. The plates were observed after a 24-hour incubation period. There was no growth in 2 of 3 plates at 30 min. and 1 of 3 plates at 60 min. of ozonation of dental instruments, thus total inhibition of the growth of 6. subtilis was not achieved. However, ozone was able to inactivate B. subtilis in water after 30- and 60 min. application since no growth occured in all replicas. One and five minutes of application of ozone is not enough to inhibit bacterial activity since all rejblicas registered positive for growth. Based on the results of this study, the portable ozone generator tested was inefficient in producing ozone at a level capable of sterilizing dental instrumehts after one hour of application.